Inflammation, Stress Response, and Redox Dysregulation Biomarkers: Clinical Outcomes and Pharmacological Implications for Psychosis - Schiavone, Stefania; Trabace, Luigia (Frontiers in Psychiatry, 2017)
In recent years, several studies claiming the finding of a specific biomarker for the identification of the “high risk state” to develop psychosis, first psychotic episode, as well as the prediction of the individual response to antipsychotics, have been published. Together with genetic reports, numerous publications in this field have been focused on inflammation and stress response blood biomarkers, as well as on indicators of redox dysregulation. In this review, we focus on human studies found in PubMed from January 1st 2010 to January 31st 2017, describing the clinical use of these biomarkers to detect the “premorbid” psychotic state and early phases of the disease. Their pharmacological implications in predicting and monitoring the individual response to antipsychotic medication is also discussed.